Inactivation kinetics of benzalkonium chloride and ethanol-based hand sanitizers against a betacoronavirus and an alphacoronavirus - Brandon L. Herdt; Luisa A. Ikner (Elsevier, 2023)
Summary: Background: Hand hygiene is critical to lower the potential for the spread of SARS-CoV-2 and other infectious agents by direct contact. When running water and soap are not available for hand hygiene, ethanol-based hand sanitizers are currently the recommended standard of care [1-3]. Though recently published data showed comparable in vitro effectiveness of benzalkonium chloride (BAK)-based and ethanol-based hand sanitizers against SARS-CoV-2 virus, a paucity of peer-reviewed data on the effectiveness of these formulations against other types of infective coronaviruses remains. This work assessed human coronavirus HCoV-229E (genus Alphacoronavirus) concurrently with SARS-CoV-2, Isolate USA-WA1/2020 (genus Betacoronavirus) to fill this gap. Methods: The test was conducted according to EN14476:2013-A2:2019 [EN14476] Quantitative Suspension Test for the Evaluation of Virucidal Activity in the Medical Area [4]. Two BAK-based hand sanitizers, five ethanol-based hand sanitizers, and an 80% ethanol reference formulation were tested for antiviral activity against SARS-CoV-2 and HCoV-229E at 15- and 30- second contact times. Results: Both SARS-CoV-2 and HCoV-229E were reduced by greater than 4.00-log10 within 15 seconds of contact. Virus decay constants (k) following first-order kinetics were similar for BAK and ethanol-based formulations against both test viruses. The SARS-CoV-2 results reported herein mirrored previous data reported by Herdt et al. (2021). Conclusion: BAK and ethanol hand sanitizer formulations inactivate SARS-CoV-2 and HCoV-229E at similar rates. This data supports previously published effectiveness data for both chemistries and indicates that additional coronavirus strains and variants would demonstrate similar inactivation trends.